Association between Health Beliefs and Medication Adherence among Hypertensive Clients in a Community Setting: A Cross-Sectional Study - Monica Artha Jelita; Dewi Hartinah; Muhamad Jauhar; Noor Eswanti (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Background.Non-adherence to hypertension treatment remains a major public health concern and is influenced by patients’ health beliefs. Objective.This study aimed to analyze the relationship between health beliefs and medication adherence among hypertension clients in the community. Methods. A correlational study with a cross-sectional design was conducted in a hypertension locus village in Kudus Regency in April 2025. A total of 80 hypertension clients were recruited using total sampling. Health beliefs were measured using the Health Belief Model (HBM) questionnaire, including perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-efficacy. Medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using the chi-square test. Results. The results showed a significant relationship between health beliefs and medication adherence (p < 0.001). Conclusions. Stronger health beliefs were associated with higher adherence to hypertension treatment. These findings highlight the importance of strengthening health beliefs to improve medication adherence and support effective hypertension management in the community.